Effects of High Dietary Inclusion of Defatted Mealworm (Tenebrio molitor) Meal as a Fish Meal Substitute on Growth, Histological Traits, and Health Performances of Rainbow Trout (Oncorhynchus mykiss) - Md. Sakhawat Hossain; Ali Hamidoghli; Jeongwhui Hong; Wendy Sealey; Brian C. Small (Aquaculture Nutrition)
The digestibility of defatted mealworm (DMW, Tenebrio molitor) and its substitution for fishmeal (FM) in rainbow trout (Oncorhynchus mykiss) diets was determined. In the first trial, a diet with 40% FM was considered as the control (Diet 1), and four other diets replaced 25% (Diet 2), 50% (Diet 3), 75% (Diet 4), and 100% (Diet 5) of FM with DMW. In the second trial, the in vivo digestibility of DMW was assessed. Results of the first trial showed no significant differences in fish growth and feed utilization performance among dietary groups (p >0.05). Fish fed the highest DMW level showed significantly higher whole-body lipid and energy composition compared to fish fed the control diet. Substitution of FM with DMW did not significantly affect hematological electrolyte, acid–base, and blood gas parameters, except for sodium (Na) concentration. The measured mean score of histopathological features did not show significant degradation of the distal intestine when FM was completely replaced. A significantly lower liver inflammation was observed in fish-fed Diet 3 compared to fish-fed Diet 5. Based on the results of the second experiment, the apparent digestibility coefficient of dry matter, protein, lipid, energy, and phosphorus were 80%, 87%, 100%, 84%, and 90%, respectively, and all essential amino acid digestibility coefficients were >90%. Overall, the highly digestible DMW can fully replace FM in the diet, up to 40% as fed, with little to no impact on the health, growth performance, feed efficiency, and fillet composition. When considering all parameters evaluated, an inclusion level between 20% and 30% (as fed) or 50%–75% of FM replacement was found to yield the best performance and fish health.